The Bronze Horse and the Lifetime of Simon the Athenian - Petrova, Valeria (Hyperboreus, 2021)
interest as one of the earliest specimens of Attic prose and the ﬁrst technical treatise dealing with horses. As the text itself does not contain any evidence which would allow establishing the author’s lifetime, scholars tend to date the passage to ca. 450–362 relying on Xen. De re equ. 1. 1, where Simon’s work is mentioned as one of the sources. Xenophon says that his predecessor dedicated a statue of a horse in Athens and had his deeds carved on its base. Simon’s monument seems to be so well-known that Xenophon mentioned it in order to identify the person in question. This paper argues that the timeframe can be made still narrower, the biography of Xenophon accurately analysed from the moment he left Athens for Asia in 401 BC. It is highly likely that he only returned home many years later (if ever), after having written that part of the treatise where Simon was mentioned. Thus, he had the last chance to see the statue as a young man (in 401 and earlier). Therefore, not the time of writing De re equestri, but Xenophon’s departure from Athens can be considered as the terminus ante quem for Simon’s activity.